2018
DOI: 10.1007/s11882-018-0785-7
|View full text |Cite
|
Sign up to set email alerts
|

SLIT’s Prevention of the Allergic March

Abstract: Several studies show the efficacy and safety profile of sublingual immunotherapy (SLIT) for the treatment of respiratory allergy diseases, but few data are available on its effect of primary and secondary prevention of allergic disease. The purpose of this manuscript is to review the latest studies addressing the effect of SLIT on the development of new sensitizations in not sensitized or already sensitized patients and progression of the allergy march.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 98 publications
0
13
0
1
Order By: Relevance
“…The prevalence of allergic diseases including allergic rhinoconjunctivitis (ARC) and allergic asthma has in recent decades increased among children and adolescents, affecting quality of life, sleeping patterns, and school performance, along with high socioeconomic costs . Furthermore, it is well established that prevalence of ARC predisposes for development of allergic asthma, pointing at the importance of intervening at an early time point. As today's treatment options for ARC mainly comprise symptomatic pharmacotherapy often accompanied by side effects, there is a great need of better treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of allergic diseases including allergic rhinoconjunctivitis (ARC) and allergic asthma has in recent decades increased among children and adolescents, affecting quality of life, sleeping patterns, and school performance, along with high socioeconomic costs . Furthermore, it is well established that prevalence of ARC predisposes for development of allergic asthma, pointing at the importance of intervening at an early time point. As today's treatment options for ARC mainly comprise symptomatic pharmacotherapy often accompanied by side effects, there is a great need of better treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy was shown to be effective in the supression of all phases of allergic responses (13) . Also immunotherapy was shown to be effective in preventing development of new sensitizations and allergies (14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual allergen immunotherapy (SLIT) comprises sublingual (oral) administration of a certain amount of allergen extract which causes the allergy [13]. However, biodistribution studies have shown the lack of systemic absorption of allergen through the oral mucosa after sublingual administration.…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
“…These antigen-specific IgG antibodies can block the allergic inflammation cascade outcome of antigen recognition by IgE. Furthermore, Tregs suppress IgE production via downregulating cytokine production in Th2 cells [13].…”
Section: Slit Mechanismsmentioning
confidence: 99%